Back Cover: Highly Chemoselective Iridium Photoredox and Nickel Catalysis for the Cross‐Coupling of Primary Aryl Amines with Aryl Halides (Angew. Chem. Int. Ed. 42/2016). Issue 42 (6th October 2016) - Oderinde, Martins S.; Jones, Natalie H.; Juneau, Antoine; Frenette, Mathieu; Aquila, Brian; Tentarelli, Sharon; Robbins, Daniel W.; Johannes, Jeffrey W.
Abstract : The cogs of Ir photoredox and Ni catalysts have been merged to provide a new and powerful approach to cross‐coupling. As described by M. S. Oderinde, J W. Johannes et al. in their Communication onpage 13219 ff., aryl amination was achieved by employing an Ir photoredox/Ni dual‐catalytic platform with inexpensive blue LED irradiation. The dual ability of the Ir complex to oxidize arylamines and reduce Ni II by an outer‐sphere single‐electron‐transfer process enabled C−N cross‐coupling under remarkably mild conditions.